Development of Aging-Related Emphysematous and Lymphoma-Like Lesions is Enhanced by the Lack of Secretoglobin 3A2 in Mouse Lungs - Kurotani R; Kurumazuka A; Sakahara S; Takakura K; Yokoyama Y; Xu L; Dai J; Lee MP; Kumaki N; Abe H; Kimura S (International Journal of COPD, 2022)
Reiko Kurotani,1 Akira Kurumazuka,1 Satoshi Sakahara,1 Kei Takakura,1 Yutaro Yokoyama,1 Lei Xu,2 Jieqiong Dai,3 Maxwell P Lee,3 Nobue Kumaki,4 Hiroyuki Abe,1 Shioko Kimura2 1Biochemical Engineering, Graduate School of Science and Engineering, Yamagata University, Yonezawa, Yamagata, 992-8510, Japan; 2Laboratory of Metabolism, National Cancer Institute, National Institutes of Health, Bethesda, MD, 20892, USA; 3Laboratory of Cancer Biology and Genetics, National Cancer Institute, National Institutes of Health, Bethesda, MD, 20892, USA; 4Department of Pathology, Tokai University School of Medicine, Isehara, Kanagawa, 259-1193, JapanCorrespondence: Reiko Kurotani, Biochemical Engineering, Graduate School of Science and Engineering, Yamagata University, 4-3-16 Jonan, Yonezawa, Yamagata, 992-8510, Japan, Tel +81-238-26-3365, Fax +81-238-26-3365, Email kurotanir@yz.yamagata-u.ac.jpBackground: Secretoglobin (SCGB) 3A2 is a novel bioactive molecule with anti-inflammatory and anti-fibrotic activities. SCGB3A2 also promotes the maturation of bronchial divergence and the lungs during embryonic development. However, much remains unknown concerning the roles of SCGB3A2 in diseases associated with aging.Methods: The lungs of Scgb3a2-knockout (KO) mice and their wild-type (WT) littermates were subjected to histological analysis, Victoria blue staining to evaluate of elastic fibers, and lung morphometric analysis during the postnatal period (birth to 8 weeks) and during aging (8 weeks to 2 years). Their spleens were also histologically evaluated. The expression of lung surfactant protein (SP) mRNAs was examined by quantitative reverse transcriptase-polymerase chain reaction. RNA sequencing (RNAseq) analysis was performed on 3-month-old KO and WT mouse lungs.Results: The alveolar spaces of KO mice continuously expanded between 0.5 and 2 years of age, accompanied by increases of the mean linear intercept and destructive index. KO mouse lungs displayed inflammation associated with lymphocyte aggregate starting at 1 year of age, and the inflammation was worse than that of WT mouse lungs. A high number of lymphoma-like cells were presented in 2-year-old KO mouse lungs. White pulp fusion was detected in the spleens of both WT and KO mice older than 0.5 years; however, the fusion was more severe in KO mice than in WT mice. The expression of surfactant protein (SP)-A, SP-B, SP-C, and SP-D mRNAs in KO mouse lungs decreased with age, and after 1 year of age, the expression of most SPs was significantly lower in KO mice than in WT mice. RNAseq demonstrated that the expression of immune system-related genes was highly altered in KO mouse lungs.Conclusion: SCGB3A2 may be required for maintaining homeostasis and immune activity in the lungs during aging. SCGB3A2 deficiency might increase the risk of emphysema of the lung.Keywords: secretoglobin 3A2, aging, pulmonary emphysema